Left Ventricular Deformation and Myocardial Fibrosis in Patients With Advanced Heart Failure Requiring Transplantation - Cameli, Matteo; Mondillo, Sergio; Righini, Francesca Maria; Lisi, Matteo; Dokollari, Aleksander; Lindqvist, Per; Maccherini, Massimo; Henein, Michael (Journal of cardiac failure, 2016)
•Patients with extensive fibrosis had worse left ventricular (LV) global longitudinal strain (GLS) and global circumferential strain compared with those with less fibrosis.•LV myocardial fibrosis strongly correlated with GLS but did not correlate with LV ejection fraction.•GLS is the most accurate LV global function measure in advanced systolic heart failure. To evaluate potential relationships between different components of left ventricular (LV) function and histopathological evidence for myocardial fibrosis in patients undergoing heart transplantation. The study population included patients with advanced heart failure, referred for an echocardiographic examination before heart transplantation. Traditional LV function measurements and global longitudinal strain (GLS) by speckle tracking echocardiography, averaging all LV segments in 4-, 2-, and 3-chamber views were obtained in all subjects. LV tissue samples were obtained from all patients who underwent heart transplantation. Myocardial fibrosis was assessed using Masson's staining. Of 106 patients referred for cardiac transplantation, 47 underwent cardiac transplantation and were enrolled in the study. LV myocardial fibrosis and its grade strongly correlated with GLS (r = 0.75, P = .0001), modestly with global circumferential strain and LV torsion (r = 0.61, P = .001 and r = 0.52, P = .01, respectively) and weakly with mitral S′ wave (r = −0.41; P = .01) and mitral annular plane systolic excursion (r = −0.35; P = .05) but did not correlate with LV ejection fraction (r = −0.12; P = NS). GLS had the strongest accuracy for detecting LV fibrosis (area under the curve, 0.92). None of the echo parameters correlated with patient's exercise capacity. Global longitudinal strain is the most accurate LV global function measure that correlates with the extent of myocardial fibrosis in patients with advanced systolic HF requiring heart transplantation.